Pré-Textuais - Silveira, Claudinei Taborda da; Sopchaki, Carlos Henrique; Silveira, Ricardo Michael Pinheiro; Neuman, Gisele (Ra'e Ga: o Espaço Geográfico em Análise, 2014)
Claudinei Taborda da Silveira, Carlos Henrique Sopchaki, Ricardo Michael Pinheiro Silveira, Gisele Neuman.